Peran Penerimaan Diri Dalam Meningkatkan Kualitas Hidup Pasien Penyakit Degeneratif Di Rs Bhirawa Bhakti Kota Malang - Badrus Sholeh, Muhammad; Priasmoro, Dian Pitaloka; Patria, Dion Kunto Adi (Jurnal Keperawatan Muhammadiyah, 2024)
This study aims to identify the relationship between self-acceptance and the quality of life of patients with degenerative diseases in the Internal Medicine Polyclinic Room, Bhirawa Bhakti Hospital, Malang City. The design of this study uses cross sectional. The population is 80 patients in the Internal Medicine Poly Room. The sampling technique used is consecutive sampling. This research was conducted from 01 to 05 July 2024. The research instrument used a questionnaire sheet and the variable studied was self-acceptance. Data analysis uses univariate and bivariate data analysis. The results of the study showed the relationship between self-acceptance and the quality of life of degenerative disease patients in the Internal Polyclinic with a total of 35 respondents, the results were obtained that changes in self-acceptance were significantly related to changes in quality of life in the samples studied with data on the sig value (2-Tailed) of 0.001 (p< 0.05), meaning that self-acceptance was significantly related to quality of life. From the results of the study, it is hoped that families can provide support and motivation to respondents to remain enthusiastic about living life and provide support so that they can improve the quality of life of patients for the better.